Malaria burden and associated risk factors among malaria suspected patients attending health facilities in Kaffa zone, Southwest Ethiopia - Aster Alemu; Beshada Lemma; Temesgen Bekele; Geleta Geshere; Eba Alemayehu Simma; Chernet Tuge Deressa; Tsige Ketema (Malaria Journal)
Abstract Background Ethiopia has been progressing very well in controlling malaria in the past few years. However, shortly after the COVID-19 pandemic, an unpredictable malaria resurgence was observed in almost all malaria-endemic areas of the country, although the exact cause of which has not yet been identified. Therefore, this study aimed to investigate malaria burden and associated risk factors in one of the endemic zones of Ethiopia. Methods A health facility-based retrospective and cross-sectional study design was conducted in the Kaffa zone, southwest of Ethiopia. Hence, a seven-year retrospective data on malaria positivity rate, interventional activities undertaken in the area, and climatic variables were collected from the patient's medical records, district health bureau, and meteorological institute, respectively. For the cross-sectional study, all malaria-suspected patients seeking medication at the health facilities in the Kaffa Zone administrative centre, Bonga town, during the study period (January–June 2024), were recruited in the study. Data on the patient's socio-demographic, socio-economic, behavioural, health facilities and environmental factors were collected using a structured face-to-face interview questionnaire. Data was analysed using Statistical Package for Social Science software (SPSS) (version 26) and the statistical tools used were descriptive statistics and logistic regression models. A significant level was considered at p < 0.05. Results The study findings revealed a significant increment in malaria positivity trend (39.43%, n = 188,201/477,276, p < 0.0001) between July 2018 and June 2024. Also, the malaria positivity rate documented in the cross-sectional study was 50.72% (n = 315/621). Plasmodium falciparum was the dominant malaria parasite. The study identified weakened control measures (p = 0.006), limited awareness of the population (p < 001), and socio-demographic factors such as education (p = 0.037), age (p = 0.008), housing condition (p < 0.0001), low-income level (p < 001), and travel history to malaria-endemic areas (p = 0.001)] as risk factors associated with high malaria positivity rate. In addition, indoor residual spraying (IRS) and mean maximum temperature activity increased by 1 unit, and the malaria positivity rate decreased by 28 times (p < 0.0001) and 1.3 (p = 0.003), respectively. The months of July and September were strongly and positively associated with higher malaria positivity in the area (p < 0.05). Conclusion Even though Ethiopia was able to achieve a remarkable malaria burden reduction in the past few years, the recent interrupted malaria control activities, seasonal variability, and patient and health facility-associated factors have contributed to the current high malaria positivity rate documented in Kaffa zone, Southwest Ethiopia. This urges the need for immediate community sensitization activities to enhance the awareness of malaria, besides designing integrated vector control interventional strategies to tackle the current alarming situation in the zone.